If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + y = -40 Combine like terms: 3y + y = 4y 4y = -40 Solving 4y = -40 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '4'. y = -10 Simplifying y = -10
| -3(1-n)=6-6n | | 10(v+2)-4v=3(2v+1)-12 | | 17-5(-7-8)+1= | | b-34=11 | | 6x+29=-4x | | 500+35g=55h | | w+-30=-52 | | 34=y-18 | | 7y=-98 | | b+13=42 | | -56=74+10x | | -3(2x-2)=24 | | 8t-10-2t=-6+10+9t | | 6y+3x=22 | | x+10(x+1)+5=550 | | 2y+4x=12.50 | | a^2+6a=7 | | -(5-3x)+x=4 | | 2r^3+8r^2+6r=0 | | -3.4x=36 | | x+64=x+59 | | x+64+x+59=75 | | -53=90-11x | | x+64+x+59+75=180 | | 18+6g=2(4c+5) | | 5.9x-1=12.7+6.2 | | -6-3(2k+4)=14 | | 3(a-4)=-21 | | 3y^2+3y-18=0 | | 12r-9=6r+18 | | 15=a+24 | | 7m-17=6 |